Distinct histological patterns in chronic hepatitis D with nucleos(t)ide analogue therapy - Hercun, Julian; Heller, Theo; Glenn, Jeffrey S.; Kleiner, David E.; Koh, Christopher (Frontiers in Medicine, 2023)
Background: Chronic hepatitis delta virus (HDV) infection leads to a more severe hepatitis than hepatitis B virus (HBV) infection alone. Specific histological staining patterns have been described in HBV mono-infection, however this has not been extensively investigated in HDV co-infection. This study evaluated whether the use of nucleos(t)ide analogs (NAs) for concurrent HBV infection has an impact on the histological appearance of chronic HDV. Methods: Liver biopsies of all patients referred for management of HDV infection were reviewed and hepatitis-specific stains for HBV antigens were evaluated. Clinical and histological characteristics were compared between patients on and off-NA therapy. Results: 50 patients were included in our analysis, of which 26 (52%) were on NA therapy at the time of the biopsy. Overall, 8% stained for HBV core antigen and 86% stained for HBV surface antigen. On and off-NA groups had similar degrees of fibrosis and inflammation, however NA patients had an odds ratio of 7.15 for membranous staining and 0.13 for scattered granular staining (p=0.001). No association was found with markers of disease severity or viral activity, with nonetheless a lower score of total inflammation noted in biopsies with a positive membranous stain (8.5 vs 10.3 p=0.04) Conclusions: In chronic HDV infection, patients treated with nucleos(t)ide analogs demonstrate a unique membranous staining pattern for hepatitis B surface antigen, which is not associated with HBV or HDV replicative activity. These findings may help improve the understanding of the role of HBV directed therapy in HDV pathophysiology.